Characterization of thermal conductivity and viscosity of alumina nanocoolant with ethylene-glycerol based fluid for quenching process - Yusoff, A. R.; Yusoff, Wan Azhar; Azmi, W. H.; Shaharudin, Mohd Ali Hanafiah; Osman Zahid, Muhammed Nafis; Hamedon, Zamzuri B.
This dispersed Al2O3 nanoparticles from the range of 0.2 to 1.0% volume concentration with an average diameter of 13 nm into three volume percentages of water to ethylene glycol such as 60%:40%, 50%:50%, and 40%:60%. The heat transfer distribution of the hot blanks with nanocoolant and chilled water are simulated for transient thermal analysis in finite element simulation via ANSYS to evaluate the enhancement of convection heat transfer coefficient and determine the optimum cooling rate of cooling system in HPF tool. It was found that the highest enhancement of thermal conductivity was observed to be 10% higher than base fluid for 1.0% volume concentration of Al2O3 at 55 °C in 60%:40% (W/EG). The pattern of the temperature distribution of the finite element analysis model was in agreement with the experimental results. The tensile strength and Vickers hardness values of the hot pressed parts were evaluated to be approximately 1,550 MPa and 588 HV, respectively.